Big G - Lydia Cox; Gernot Müller; Ernesto Pasten; Raphael S. Schoenle; Michael Weber; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2020)
"Big G" typically refers to aggregate government spending on a homogeneous good. In this paper, we open up this construct by analyzing the entire universe of procurement contracts of the US government and establish five facts. First, government spending is granular, that is, it is concentrated in relatively few firms and sectors. Second, relative to private expenditures its composition is biased. Third, procurement contracts are short-lived. Fourth, idiosyncratic variation dominates the fluctuation of spending. Last, government spending is concentrated in sectors with relatively sticky prices. Accounting for these facts within a stylized New Keynesian model offers new insights into the fiscal transmission mechanism: fiscal shocks hardly impact inflation, little crowding out of private expenditure exists, and the multiplier tends to be larger compared to a one-sector benchmark aligning the model with the empirical evidence.
Keywords: E62; E32; 330; government spending; federal procurement; granularity; sectoral heterogeneity; fiscal policy transmission; monetary policy